TECHNOLOGICAL INNOVATIONS OF THE ERA OF THE QUANTUM ECONOMY (Development Service Industry Management, 2023)
The article examines the influence of quantum technologies on modern economic development. To achieve the goal, the main trends in quantum technologies, quantum computing, quantum cryptography and communications, which revolutionize data processing and create new protection conditions, were analyzed. The characteristics of the quantum economy as the basis of further technological revolutions, which globally reform individual branch systems and the global system of economic development, are considered. In the course of the study, attention is paid to the description of the properties of quantum technology and the practical approach to its application, which began at the beginning of the 20th century. Quantum computing is defined as a technology that uses quantum mechanical phenomena to perform operations on data. Quantum computers provide advantages in solving tasks that are inaccessible to classical systems. In finance, quantum computers optimize models and analyze the market. In science, quantum computers are used to model molecular structures, which accelerates the creation of materials with desired properties. Quantum communication uses quantum states of information transfer, which makes the process extremely secure and confidential. The basis of quantum communication is entanglement, which allows the states of two qubits to communicate regardless of the distance. Quantum sensors are devices that use quantum phenomena to measure physical quantities with high precision. Quantum materials have the properties of the quantum mechanical effect; include the latest types of superconductors and produce lossless energy and revolutionize power transmission technologies.The result of the research is recommended for further scientific developments in the adoption of innovative solutions in the quantum economy. The conclusion of the study is the quantum economy as the beginning of the newest era of technological development, which provides prospects and foresees a breakthrough in the implementation of the laws of nature, allows the creation of the latest goods, services, and business models. The findings suggest that global partnerships, concerted action by governments, business and the scientific community, are key to creating a secure quantum future and a sustainable economy. New methods of problem-solving are inaccessible to classic computer technologies, generate resources in the conditions of big data and quantum computing, which are characterized by a high level of dynamism and novelty.
Keywords: quantum economy; quantum technologies; quantum computing; quantum cryptography; quantum communication; technological revolution; global economic system